Distributional Effects of Globalization in Developing Countries - Goldberg, Pinelopi Koujianou; Pavcnik, Nina (Journal of Economic Literature, 2007)
The authors discuss recent empirical research on how globalization has affected income inequality in developing countries. They begin with a discussion of conceptual issues regarding the measurement of globalization and inequality. Next, they present empirical evidence on the evolution of globalization and inequality in several developing countries during the 1980s and 1990s. The authors then examine the channels through which globalization may have affected inequality, discussing theory and evidence in parallel. They conclude with directions for future research.